2019
DOI: 10.1186/s12955-019-1102-4
|View full text |Cite
|
Sign up to set email alerts
|

Can physical activity compensate for low socioeconomic status with regard to poor self-rated health and low quality-of-life?

Abstract: BackgroundBoth high socioeconomic status (SES) and high physical activity (PA) are associated with better self-rated health (SRH) and higher quality-of-life (QoL).AimTo investigate whether high levels of PA may compensate for the association between low SES and subjective health outcomes in terms of poorer SRH and lower QoL.MethodData from a cross-sectional, population-based study (n = 5326) was utilized. Multiple logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
2
20
2
1
Order By: Relevance
“…Health inequalities are also reflected in poorer self-perceived health in individuals with a low SEP compared to individuals with a high SEP ( Eurostat, 2018 ), and self-perceived health is an important predictor of future morbidity and mortality ( Reile et al, 2017 ). Workplace health promotion programs aiming to promote healthy behavior are considered promising to improve self-perceived health of employees with a low SEP, as poorer health behavior, which is more common in individuals with a low SEP, is a known risk factor of a poor self-perceived health ( Goldstein et al, 1984 ; Johansson et al, 2019 ; Manderbacka et al, 1999 ; Shields and Shooshtari, 2001 ). However, it has rarely been evaluated to what extent workplace health promotion programs focusing on promoting healthy behavior actually do improve self-perceived health of employees with a low SEP.…”
Section: Introductionmentioning
confidence: 99%
“…Health inequalities are also reflected in poorer self-perceived health in individuals with a low SEP compared to individuals with a high SEP ( Eurostat, 2018 ), and self-perceived health is an important predictor of future morbidity and mortality ( Reile et al, 2017 ). Workplace health promotion programs aiming to promote healthy behavior are considered promising to improve self-perceived health of employees with a low SEP, as poorer health behavior, which is more common in individuals with a low SEP, is a known risk factor of a poor self-perceived health ( Goldstein et al, 1984 ; Johansson et al, 2019 ; Manderbacka et al, 1999 ; Shields and Shooshtari, 2001 ). However, it has rarely been evaluated to what extent workplace health promotion programs focusing on promoting healthy behavior actually do improve self-perceived health of employees with a low SEP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to the fteen parkruns completed per year on average, this would equate to another 111 days per year of activity outside parkrun; this increases to 115 days per year if they are also from socioeconomically deprived areas. Given that individuals living in more socioeconomically disadvantaged areas who are physically active may experience better health and quality of life than their neighbours who are less active (14), further research is needed to explore how community physical activity initiatives like parkrun can use strategies which promote inclusivity.…”
Section: Discussionmentioning
confidence: 99%
“…parkrun data shows that only 13.1% of those participating at least once live in the most socioeconomically deprived areas of the UK (see Table 1a). Previous surveys have demonstrated that individuals who live in economically deprived areas and are physically active may experience much better health and quality of life than their neighbours who are less active (14). In a cohort study of 354 new parkrun participants in the UK, Stevinson and Hickson (15) also showed that parkrun participation is associated with signi cant positive changes in health and wellbeing over 6 and 12 months, including level of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies demonstrated a direct relationship between level of physical activity and positive health perception in adults and older adults ( Johansson et al, 2019 ; Cui et al, 2020 ; Han, 2020 ; Sperlich et al, 2020 ; Yaya & Bishwajit, 2020 ), and the high level of physical activity is a factor that compensated for the low socioeconomic level in the self-rated health status ( Johansson et al, 2019 ). However, most studies have analyzed the level of general physical activity (without specifying domains) ( Johansson et al, 2019 ; Cui et al, 2020 ; Han, 2020 ; Yaya & Bishwajit, 2020 ), or when analyzed physical activity domains, they did not report what would be the types (modalities) of physical activities practiced ( Sperlich et al, 2020 ). The results found are relevant, as they strengthen the importance of regular physical activity in the positive health perception.…”
Section: Introductionmentioning
confidence: 99%